The Relationship Between Malaria Parasite Density and Anemia Status in Mau Bokul Village, Pandawai District, East Sumba - Parera, Maria Albertini Elfrida; Deo, Dwita Anastasia; Jannah, Insani Fitrahulil; Adang, Gottfrieda Patiencia Taeng-Ob (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Malaria remains a major public health problem in eastern Indonesia, and anemia is a frequent complication among infected individuals. Objective: To analyze the correlation between Plasmodium parasite density and anemia status among residents of Mau Bokul Village, East Sumba. This quantitative study employed a cross-sectional design with consecutive sampling and included 194 respondents. Malaria diagnosis was established through microscopic examination of Giemsa 3%–stained thick blood smears, while hemoglobin levels were measured using a digital device. The association between variables was analyzed using Spearman’s correlation test (p < 0.05). The findings showed a malaria prevalence of 4.1% (8/194), while anemia was identified in 17.52% (43/194) of respondents. All malaria-positive individuals were anemic, with a mean hemoglobin level of 7 g/dL, and most were classified as having severe anemia. Spearman’s test revealed a significant negative correlation between parasite density and hemoglobin levels (r = –0.318; p < 0.001), indicating that increasing parasite density is associated with decreasing hemoglobin concentrations. Parasite density shows a positive correlation with anemia status, underscoring the need for strengthened malaria control and anemia management in endemic settings. Recommendations: Integrate routine Hb screening in malaria case management and reinforce vector control and chemoprevention strategies.